The "Conducive Situation" in the Context of Abuse and the Catholic Church: Exploring Integral Theories of Sexual Violence and Ecclesiologies Supporting Clerical Abuse - Lledo Gomez, Cristina (Buddhist Christian studies, 2021)
This article is concerned with the power of the situation in the sexual abuse of children in religious institutions, particularly in the Catholic Church. While I primarily write from an Australian Catholic theological-ecclesiological lens, this article can have much relevance for other religious institutions in other countries, trying to make sense of abuse in their own institutions. This article begins with the context of child sexual abuse (CSA) in the Australian Roman Catholic Church. The context is broadened to show that CSA is part of a wider practice in the world, as shown in integral theories of sexual violence and abuse. Within these integral theories of violence are the factors of the "opportunity" and the "conducive situation" which together enable circumstances of abuse of power by Church clergy. This article then explores other research showing the power of opportunity and the conducive situation. As a theologian specializing on the study of the Church, the rest of this article focuses on the theologies that lead to the opportunities and conducive situation for the sexual perpetration by clerics in the Catholic Church. This article briefly concludes with a practical suggestion, a way forward that can help religious institutions create a culture of safety, in turn, minimizing the "opportunity" and the "conducive situation" that lead to abuse.